2019
DOI: 10.1038/s41598-019-45214-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the hormetic influence of biosynthesized AgNPs on regenerating rice calli of indica cv. IR64

Abstract: Rice is one of the most widely cultivated crops worldwide; however, it is not amenable to genetic manipulations, owing to its poor response to tissue culture and regeneration in vitro . To improve its response to tissue culture, we evaluated the influence of biosynthesized silver nanoparticles on callus induction, regeneration and rhizogenesis in Indica rice cv. IR64. Silver nanoparticles were biosynthesized by using silver nitrate and Parthenium hysterophorus plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…It reveals that fortification of tissue culture media with silver nanoparticles (AgNPs) improves vigor and regeneration frequency of explants, mainly because of higher ability of silver ions to inhibit ethylene biosynthesis. 43 , 50 , 71 Manickavasagam et al 72 reported that biosynthesized silver nanoparticles when supplemented in tissue culture media promote callus induction frequency, callus regeneration and rhizogenesis along with significant decrease in concentration of reactive oxygen species, hydrogen peroxide and malondialdehyde in Menthalongi folia . A significant increase in callus induction and callus growth rate of Phaseolus vulgaris is reported in response to exposure of explants to 50 mg/l AgNPs for 30 min, while higher concentration were found detrimental for callogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It reveals that fortification of tissue culture media with silver nanoparticles (AgNPs) improves vigor and regeneration frequency of explants, mainly because of higher ability of silver ions to inhibit ethylene biosynthesis. 43 , 50 , 71 Manickavasagam et al 72 reported that biosynthesized silver nanoparticles when supplemented in tissue culture media promote callus induction frequency, callus regeneration and rhizogenesis along with significant decrease in concentration of reactive oxygen species, hydrogen peroxide and malondialdehyde in Menthalongi folia . A significant increase in callus induction and callus growth rate of Phaseolus vulgaris is reported in response to exposure of explants to 50 mg/l AgNPs for 30 min, while higher concentration were found detrimental for callogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of AgNPs' was also investigated in callus induction of Oryza sativa cv. IR64; where the highest callus induction was observed at a relatively low concentration of AgNPs [47]. The callus induction increased significantly as compared to that in the control medium.…”
Section: Silver-nanoparticles In Crop Improvementmentioning
confidence: 92%
“…Another possible mechanism of growth stimulation mediated by AgNPs, can be ascribed to PGR-responsive gene expressions. As a matter of fact, investigations demonstrated that these nanoparticles decreased the expression of ethylene-and ABA-responsive genes, resulting in callus regeneration rate [47]. Under closed container culture conditions, plant development will be highly influenced by self-produced gases, such as ethylene, which possibly regulate senescence.…”
Section: Possible Mechanism Of Agnps In Plant Cellsmentioning
confidence: 99%
“…m 2 /s, 16/8 h photoperiod) conditions at 25±2°C for 14 days. After a cultivation period of 13–16 days, embryogenic callus induced from explants were achieved [ 32 ]. Callus induction frequency was calculated using the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…SRMI (MS+ 0.5mg/L BAP), SRMII (MS+ 1 mg/L BAP+ 0.5 mg/L Kn) supplemented with different concentrations of IONPs (1–20 mg/L) and without IONPs as control. The regeneration frequency was observed as the percentage of chickpea explants respond to the development of shoot after 14 days [ 32 ]. The regeneration frequency was calculated using the formula given below: …”
Section: Methodsmentioning
confidence: 99%